Examining Muslim Friendly Tourism as a Strategy to Embrace Halal Tourism Prospects - Hilma Regita Syaharani; Farih Fahmi, Moh (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
The high anticipation over tourism activities has given birth to a new industry within tourism which is the development of tourism village. This is expected to encourage a sustainable tourism such as the creation of Muslim-friendly tourism segment. This research applies a new criterion and assessment indicator that is more comprehensive and updated in order to measure the compatibility of tourist destination with the standard of global halal tourism. This research aims at observing efforts to develop a Muslim-friendly tourist destination in Desa Wisata Ketapanrame (The tourism village of Ketapanrame). The approach implemented in the research is qualitative approach with phenomenology and employs primary data. The result of the research indicates that the Ketapanrame village is a tourist destination that implements the Islamic sharia principles shown by adequate facilities of worship and certified halal food. Bowever, the Village of Ketapanrame has not comprehensively fulfilled the halal tourism standard such as partitioning the swimming pool and a number of other regulations in order to comply with through sharia regulation. The assessment on the tourism village displays that even though there have been significant efforts to create a friendly environment for Muslim tourists, there are still a number of areas that require improvements in order to achieve higher standards.